Manual of chronic total occlusion interventions : a step-by-step approach - Brilakis, Emmanouil S.; ScienceDirect eBooks (London : Academic Press is an imprint of Elsevier, 2018)
"Manual of Coronary Chronic Total Occlusion Interventions: A Step-by-Step Approach, Second Edition, is an easy to read reference for coronary chronic total occlusion interventions (CTO). Written by recognized national and international experts in the field, this reference compiles the steps necessary to preform, what pitfalls to watch out for, and troubleshooting tactics necessary for coronary chronic total occlusion interventions (CTO). This second edition is updated with new developments in the field. The 2nd edition covers techniques like the Carlino technique, "scratch and go", "BASE", double-blind stick and swap, and subintimal crush, along with tips about how to use the latest complex PCI equipment. It also covers recently published trials, CTO scores and hybrid series"--Publisher's description.
When to perform chronic total occlusion interventions -- Equipment -- The basics : timing, dual injection, studying the lesion, access, anticoagulation, guide support, trapping, pressure and electrocardiogram monitoring -- Antegrade wire escalation : the foundation of chronic total occlusion percutaneous coronary intervention -- Antegrade dissection/reentry -- The retrograde approach -- Putting it all together : the hybrid approach -- "balloon-uncrossable" and "balloon-undilatable" chronic total occlusions -- Complex lesion subsets -- Radiation management during chronic total occlusion percutaneous coronary intervention -- Stenting of chronic total occlusion lesions -- Complications -- How to build a successful coronary chronic total occlusion program -- Equipment commonly utilized in CTO interventions -- Commonly used acronyms in CTO interventions.
Includes bibliographical references.
Online resource; title from electronic title page (ClinicalKey, viewed December 15, 2017).
Elsevier
Elsevier
Keywords: Coronary heart disease -- Surgery; Arterial occlusions; Coronary Occlusion -- surgery; Coronary Vessels -- surgery; Vascular Surgical Procedures -- methods; MEDICAL -- Surgery -- General; Arterial occlusions; Coronary heart disease -- Surgery; Electronic books